Influenza Vaccine Uptake in Italy—The 2022–2023 Seasonal Influenza Vaccination Campaign in Italy: An Update from the OBVIOUS Project - Angelo Capodici; Aurelia Salussolia; Giusy La Fauci; Zeno Di Valerio; Marco Montalti; Anna Odone; Claudio Costantino; Heidi J. Larson; Julie Leask; Jacopo Lenzi; Lamberto Manzoli; Davide Gori; et al. (Vaccines, 2024)
Influenza is a significant public health concern, with Italy being profoundly impacted annually. Despite extensive vaccination campaigns and cooperative initiatives between the Public Health Departments of Local Healthcare Authorities and family physicians, low vaccine uptake rates persist. This study builds upon the OBVIOUS project, providing an updated picture of influenza vaccine uptake in Italy through a representative sample. A cross-sectional computer-assisted web interviewing (CAWI) survey of 10,001 Italian citizens was conducted between 31 March and 5 June 2023. Our findings underscore the negative impact of a lack of awareness that a person is in a priority group for influenza vaccination (−26.1 percentage points in vaccine uptake) and the profound influence of social circles on vaccination decisions (−5 percentage points when unfavorable). Medical professionals played a pivotal role, with recommendations from family doctors significantly promoting vaccine uptake (+20.2 percentage points). Age, chronic conditions, and socio-demographic factors also influenced vaccination behaviors. For children, parental negative perceptions regarding the flu (−10.4 percentage points) and vaccine safety (−23.4 percentage points) were crucial determinants. The present study emphasizes the need for a comprehensive approach addressing awareness, societal beliefs, and tailored medical advice to enhance vaccination rates and protect public health in Italy.